He Tamariki Kokoti Tau: Tackling preterm incidence and outcomes of preterm births by ethnicity in Aotearoa New Zealand 2010–2014. Issue 2 (27th August 2021) - Edmonds, Liza Kathleen; Sibanda, Nokuthaba; Geller, Stacie; Cram, Fiona; Robson, Bridget; Filoche, Sara; Storey, Francesca; Gibson‐Helm, Melanie; Lawton, Beverley
Abstract: Objective: To explore preterm birth among Māori indigenous peoples through Kaupapa Māori research of preterm birth in Aotearoa New Zealand. Methods: Linked maternity, mortality, and hospital data were analyzed for women and their infants born between January 1, 2010 and December 31, 2014. Relative risks (RR) were calculated for each ethnic group for preterm birth, small for gestational age (SGA), and mortality. Results: Adjusted rates showed that compared with Māori women, European women were at significantly less risk of having extremely and very preterm infants (RR 0.86, 95% confidence interval [CI] 0.76–0.95). Preterm infants of European women had a significantly lower adjusted RR of early neonatal death (RR 0.65, 95% CI 0.45–0.93) or post‐neonatal death (RR 0.41, 95% CI 0.26–0.64). In addition to ethnicity, preterm rates were influenced by maternal age, body mass index, smoking status, and SGA status. Conclusion: This study demonstrates that the Aotearoa New Zealand maternity system privileges whiteness, suggesting that clinical pathways for evidence‐based medical care are not delivered systemically and equitably for all. Health pathways that focus on equity as a fundamental right will enhance health outcomes for Māori women and their infants. Synopsis: The Aotearoa maternity system consistently advantages privileged populations, primarily European women. Health providers should support initiatives to ensure equitable outcomes for indigenous women and infants.